ATM application using Mykad (APMY) - Nabila, Sharudin (2011)
This report is basically about ATM Application using MyKad. ATM Application using MyKad (APMY) is a system that upgrades the user convenience in using ATM.Besides that,in by replacing bankeard with MyKad,bankcard fraud can be reduced as Mykad is more secured.The existing ATM (Automated-Teller Machine) has weaknesses that should be overcomed.APMY is the best solution in order to prevent fraud from happening most of the time.Account holder that owns a MyKad is able to use this system.Compared to the old ATM system,APMY uses newly developed technology which is the MyKad which is more reliable than bankcard. MyKad,or Government Multipurpose Card,(GMPC) is the official compulsory identity card of Malaysia. It i regarded as the world's first smart identity card.So there is no burden in using MyKad because it must be carried around all the time.This system can only be used by Malayan Banking Berhad(MAYBANK) account holders and owns a MyKad.APMY is a standalone system which will be installed in the computer to use it.The system implementation requires usage of smart card reader such as EZIOOPU,MyKad and a computer.In developing this system,Rapid Application Development (RAD) is chosen as the methodology.As a conclusion, APMY is build to improvise the user convenience in ATM usage and reduce number of cases of bankcard cloning.